Changes over 6 years in secondary health conditions and activity limitations in older adults aging with long‐term spinal cord injury. Issue 2 (19th March 2022) - Waller, Mikael; Jörgensen, Sophie; Lexell, Jan
Abstract: Background: The number of individuals aging with long‐term spinal cord injury (SCI) is increasing. Still, there is limited knowledge about changes in secondary health conditions (SHCs) and activity limitations over time. Objectives: To determine changes in SHCs and activity limitations in older adults aging with long‐term SCI over 6 years, and to investigate how changes in SHCs and activity limitations are associated with gender, age, and injury characteristics. Design: Longitudinal cohort study from the Swedish Aging with Spinal Cord Injury Study (SASCIS). Setting: Community settings, Sweden. Participants: From the initial 123 participants in the SASCIS: 78 individuals (32% women); mean age 68 years; mean time since injury 31 years; injury levels C1‐L3, AIS A‐D. Interventions: Not applicable Main Outcome Measure: Bowel and bladder function and problems, pain, spasticity, and the Spinal Cord Independence Measure (SCIM III). Results: Over 6 years, bowel‐related problems increased (31% to 47%, p  = .015) and the occurrence of constipation doubled to 24% ( p  = .013). There were increases in frequent urinary tract infections (10% to 26%, p  = .004), use of indwelling urinary catheters (15% to 23%, p  = .031), and other bladder‐related problems (4% to 22%, p  < .001). The occurrence of pain was high (85%), with no significant change. Spasticity increased from 41% to 62% ( p  < .001). Activity limitations increased (SCIM III total score mean 67 to 61, p  < .001, with significant decreases in all subscales). The increase in bowel‐related problems was greater in males, and the deterioration in self‐care was greater in participants with longer time since injury and with traumatic injuries. Conclusions: These findings support the notion that SHCs and activity limitations increase over time in older adults aging with long‐term SCI. The results can inform clinicians and call for a proactive, holistic approach in the long‐term follow‐up to support healthy and active aging.